2013
DOI: 10.1152/ajpcell.00379.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of omega-3 fatty acids on injury-induced epidermal growth factor receptor transactivation contribute to delayed wound healing

Abstract: Epidermal growth factor receptor (EGFR)-mediated signaling is required for optimal intestinal wound healing. Since n-3 polyunsaturated fatty acids (PUFA), specifically docosahexaenoic acid (DHA), alter EGFR signaling and suppress downstream activation of key signaling pathways, we hypothesized that DHA would be detrimental to the process of intestinal wound healing. Using a mouse immortalized colonocyte model, DHA uniquely reduced EGFR ligand-induced receptor activation, whereas DHA and its metabolic precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 55 publications
3
44
0
1
Order By: Relevance
“…In colonic cells, DHA reduces wound-induced EGFR transactivation. Moreover, under wounding conditions, the suppression of EGFR activation is associated with a reduction in downstream activation of cytoskeletal remodeling proteins such as Rac1, as well as a reduced cell migration [22]. These observations are consistent with our findings in human airway cells and suggest that inhibition of both EGFR transactivation and downstream signaling by DHA could be independent of the cell type.…”
Section: Discussionsupporting
confidence: 91%
“…In colonic cells, DHA reduces wound-induced EGFR transactivation. Moreover, under wounding conditions, the suppression of EGFR activation is associated with a reduction in downstream activation of cytoskeletal remodeling proteins such as Rac1, as well as a reduced cell migration [22]. These observations are consistent with our findings in human airway cells and suggest that inhibition of both EGFR transactivation and downstream signaling by DHA could be independent of the cell type.…”
Section: Discussionsupporting
confidence: 91%
“…There is a growing body of experimental, epidemiological, and preclinical evidence indicating that n –3 PUFA, mainly DHA and EPA, are protective against colon tumorigenesis [9, 153157]. Establishing a causal role of n –3 PUFA in colon cancer prevention would have a major translational impact because these dietary nutrients are safe, well tolerated [158], and relatively inexpensive and provide additional health benefits, such as reduction in mortality [159].…”
Section: Resultsmentioning
confidence: 99%
“…DHA also modulates the levels and localization of a critical signaling lipid, phosphoinositide 4,5-bis-phosphate (PIP 2 ) [160••]. This in turn reduces filamentous actin remodeling as well as activation of cytoskeletal regulators, Rac1 and Cdc42, which in turn reduces cell migration [157, 160••]. Cholesterol and the cytoskeleton are major contributors to maintaining membrane order.…”
Section: Figmentioning
confidence: 99%
“…In the present study, we investigated the effect of increasing EPA+DHA content of soybean oil-based AIN-93G; however, others have investigated the lipid composition of various tissues from mice fed diets with non-standard lipid mixtures [7, 24, 25]. At least two studies that have reported the fatty acid composition of colonic mucosa where the lipid in the diet was primarily low in alpha-linolenic (ALA; 18:3n-3), such as canola or corn oil, have observed low levels of DHA (1.3% [24], 1.6% [7].…”
Section: Discussionmentioning
confidence: 99%